2009
DOI: 10.1515/cclm.2009.039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of calcium, magnesium, sodium, potassium, zinc, and creatinine concentration in 24-h and spot urine samples in women

Abstract: Although replacing burdensome 24-h urine collection with spot urine sampling might not provide the solution in all cases, our results show that for the elements analyzed, spot urine could be a reliable alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Another large study included children and measured only zinc, copper, iron, lead and cadmium. 23 Ranges have been reported for zinc 22 and iodine. 33 Generally, the ranges from our cohort agree closely with those proposed for the Reference Man and the other reported data ( Table 5).…”
Section: Discussionmentioning
confidence: 96%
“…Another large study included children and measured only zinc, copper, iron, lead and cadmium. 23 Ranges have been reported for zinc 22 and iodine. 33 Generally, the ranges from our cohort agree closely with those proposed for the Reference Man and the other reported data ( Table 5).…”
Section: Discussionmentioning
confidence: 96%
“…Forty-three papers met the inclusion criteria. Of them 23 were excluded because of lack of data and 20 were suit able for final review: 16 in adults (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and 4 in children (22)(23)(24)(25) (Figure 1). When results were reported separately for independent groups, they were entered into the tabulation as separate studies (9,13,18,19,22).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Eight studies included in the review compared 24-h urine Na contents and single spot urine Na (7,9,10,13,15,17,20,21).…”
Section: Studies Comparing 24-h With Spot Sampling In Adultsmentioning
confidence: 99%
“…The use of spot urine to replace 24 h urine collection has been studied for both Na and K in healthy populations, although most research has focused exclusively on Na (10)(11)(12)(13)(14)(15)(16) . Studies have shown good correlations between Na:creatinine and K:creatinine in spot urine and respective ratios in 24 h urine (12,14,16) .…”
mentioning
confidence: 99%